Profil Pendidikan Inklusif terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Slow Learner - Yeci Mey Linda; Hella Jusra (Universitas Muria Kudus, 2021)
This study aims to determine the profile of inclusive education in regular schools, based on policies for implementing inclusive education in every school since PPDB in 2019, as well as the mathematical problem solving abilities of slow learner inclusive students. The research method used in this research is a case study qualitative research method, where the researcher examines in depth the profile of inclusive education in the research area, the mathematical problem solving ability of slow learner students. The study was conducted at SMA Negeri 96 Jakarta, with two slow learner participants sitting in class XI MIPA, namely the first participant (SN) and the second participant (DR). Data collection techniques were carried out by observation, interviews and documentation. Data analysis before the research was conducted was used by researchers to determine slow learner participants and the place of research. analysis when the research was conducted using the Miles and Huberman model, namely data reduction, data presentation and conclusion drawing. The validity of the data was checked by data triangulation, source triangulation and time triangulation. The results of the study show that inclusive education for slow learners in regular schools is the same as regular education, there are no modifications in terms of curriculum or question instruments, as well as completeness standards. The mathematical problem solving ability of slow learner students is in the moderate to low range, this is based on the difficulty of slow learners in making mathematical models.